2021
DOI: 10.1126/scitranslmed.abl4580
|View full text |Cite
|
Sign up to set email alerts
|

Hippocampal cAMP regulates HCN channel function on two time scales with differential effects on animal behavior

Abstract: cAMP-mediated effect on HCN channel surface trafficking and mouse behavior depends on activation time scale.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(31 citation statements)
references
References 97 publications
3
28
0
Order By: Relevance
“…Knockdown (8,13) or knockout (KO) (15) of hippocampal HCN channels has been associated with an increase in antidepressant-like behavior (behavior that is similar to that of an animal given an antidepressant such as fluoxetine (16)). Moreover, we recently reported an increase in HCN channel expression in the postmortem hippocampi of human patients with MDD, which is consistent with findings from animal models of chronic stress (8,17,18). Although, these results suggest that directly targeting HCN channels with a small molecule antagonist could be an effective antidepressant strategy, HCN channels are also expressed in cardiac tissue where they play an essential role in pacemaking (19,20).…”
supporting
confidence: 87%
“…Knockdown (8,13) or knockout (KO) (15) of hippocampal HCN channels has been associated with an increase in antidepressant-like behavior (behavior that is similar to that of an animal given an antidepressant such as fluoxetine (16)). Moreover, we recently reported an increase in HCN channel expression in the postmortem hippocampi of human patients with MDD, which is consistent with findings from animal models of chronic stress (8,17,18). Although, these results suggest that directly targeting HCN channels with a small molecule antagonist could be an effective antidepressant strategy, HCN channels are also expressed in cardiac tissue where they play an essential role in pacemaking (19,20).…”
supporting
confidence: 87%
“…Nonetheless, given the relevance of the dHPC to spatial memory, it is possible that the observed female-specific increase in PKA-mediated signaling may contribute to ketamine’s effects within this cognitive domain in a sex-dependent manner. Activation of PKA signaling by ketamine mediated via elevated cAMP levels is known to impact cognitive processes 67 , and spatial memory is affected by elevated dHPC cAMP levels in a biphasic manner 17 . More specifically, Lyman and colleagues (2021) recently demonstrated that acute increases in dCA1 pyramidal neurons in chronically-stressed male and female mice impaired object location memory, and blunted response to the antidepressant citalopram in this behavioral task 17 .…”
Section: Resultsmentioning
confidence: 99%
“…Activation of PKA signaling by ketamine mediated via elevated cAMP levels is known to impact cognitive processes 67 , and spatial memory is affected by elevated dHPC cAMP levels in a biphasic manner 17 . More specifically, Lyman and colleagues (2021) recently demonstrated that acute increases in dCA1 pyramidal neurons in chronically-stressed male and female mice impaired object location memory, and blunted response to the antidepressant citalopram in this behavioral task 17 . Conversely, chronically-elevated dHPC cAMP levels improved performance in the same object location memory task.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…At the behavioural level, TRIP8b expression in CA1 neurons has been linked to major depressive disorder (MDD) and human MDD patients and animal models of chronic stress exhibit higher expression of hippocampal HCN1 ( Han et al, 2017 ; Kim et al, 2018 ; Lyman et al, 2021 ). Similarly, while acute cAMP upregulation can reduce spatial memory and motivated behaviours, chronically-elevated cAMP can increase motivated behaviours, possibly through down-regulation of TRIP8b ( Lyman et al, 2021 ). And TRIP8b knockout in mice contributes to increases in motivated behaviours, including more time spent mobile in forced swim and tail suspension tests ( Lewis et al, 2011 ; Han et al, 2017 ).…”
Section: Trip8bmentioning
confidence: 99%